Exploring the Dynamics of Learning Communities in Fostering Collaboration and Knowledge Exchange - Barigai, Archita; Heravdakar, Lasya (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study explores into the dynamics of mastering groups and their impact on collaborative understanding exchange and social interplay. By conducting interviews and analyzing player statements, the research delves into the factors, obstacles, and results associated with acquiring insights into communities. The results emphasize the importance of collaboration, creativity, inclusivity, and diversity in shaping learning communities. Collaboration is essential for sharing knowledge and fostering growth, as each generation brings unique opportunities and obstacles for connecting and engaging. Recognizing inclusivity and diversity as essential elements is crucial for establishing fair and enriching learning settings. Understanding these dynamics allows educators and practitioners to cultivate vibrant learning communities that promote lifelong learning and positive social change.